Evaluation of biohydrogen production potential of fragmented sugar industry biosludge using ultrasonication coupled with egtazic acid. (6th January 2021) - Sethupathy, A.; Kumar, Paturi Syam; Sivashanmugam, P.; Arun, C.; Banu, J. Rajesh; Ashokkumar, Muthupandian
Abstract: In this study, the influence of ultrasonication (USN) combined with egtazic acid fragmentation method on sugar industry waste (SWS) sludge was studied for improving biohydrogen production. Initially, USN method was proceeded by varying power and fragmentation time. At an optimal power (115 W) and fragmentation time (30 min), USN method demanded 23, 000 kJ/kg TS specific energy for achieving 15.2% complex organics solubilization rate (COR). To further upsurge of SWS sludge solubilization, USN assisted with egtazic acid (USNEG) method was performed by varying fragmentation time and egtazic acid dosage at an optimal power (115 W). USNEG method has achieved more COR (23%) at minimum specific energy of 11, 500 kJ/kg TS (fragmentation time: 15 min and EGTA dosage: 0.03 g/g TS). Then, biohydrogen potential (BHP) assay was investigated in which USNEG method has obtained higher biohydrogen production. Also, energy analysis revealed that USNEG method exhibited an energy ratio of 1.78. Highlights: USN method demanded 23000 kJ/kg TS of specific energy for attaining 15.2% COR. USNEG method exhibited a higher COR of 23% at 11500 kJ/kg TS. A higher intracellular components release was noted for USNEG method. USNEG method was attained a higher biohydrogen production of 28 mL/g VS. USNEG method exhibited positive net energy of 2.5 kWh/kg of SWS sludge.